2017
DOI: 10.1002/aet2.10022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Socioeconomic Status Bias on Medical Student–Patient Interactions Using an Emergency Medicine Simulation

Abstract: Objectives: Implicit bias in clinical decision making has been shown to contribute to healthcare disparities and results in negative patient outcomes. Our objective was to develop a high-fidelity simulation model for assessing the effect of socioeconomic status (SES) on medical student (MS) patient care.Methods: Teams of MSs were randomly assigned to participate in a high-fidelity simulation of acute coronary syndrome. Cases were identical with the exception of patient SES, which alternated between a low-SES h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(19 reference statements)
0
7
1
Order By: Relevance
“…Medical students, in an emergency medicine simulation, were less likely to ask about pain control and more likely to touch a low SES patient (9). Also, low SES has been associated with less frequent opioid and non-pharmacological treatment prescriptions, greater prescription of generic pain medication and an increased recognition of the importance of psychoeducation (8)(9)(10)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical students, in an emergency medicine simulation, were less likely to ask about pain control and more likely to touch a low SES patient (9). Also, low SES has been associated with less frequent opioid and non-pharmacological treatment prescriptions, greater prescription of generic pain medication and an increased recognition of the importance of psychoeducation (8)(9)(10)).…”
Section: Introductionmentioning
confidence: 99%
“…Medical students, in an emergency medicine simulation, were less likely to ask about pain control and more likely to touch a low SES patient (9). Also, low SES has been associated with less frequent opioid and non-pharmacological treatment prescriptions, greater prescription of generic pain medication and an increased recognition of the importance of psychoeducation (8)(9)(10)). On the other hand, a set of vignette studies using a novel social class implicit association test did not find significant effects of patient SES nor of implicit class biases on medical students', nurses' or physicians' pain assessment and management decisions (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of implicit bias regarding race, socioeconomic status or gender varies, as some studies find biases in health professionals (Haider et al, 2015, Hall et al, 2015Johnson et al, 2017;Harris et al, 2018) while others do not (Williams et al, 2015). Another study by Pettit et al (2017) do not show any statistically significant differences in clinical care for patients with different socioeconomic status. However, they do show different behavioural patterns towards patients with a higher socioeconomic status such as a better communication or an increased attentiveness to pain control.…”
Section: Empirical Data On the Prevalence Of Decision-making Biases In Medicinementioning
confidence: 96%
“…While there is no clear evidence that implicit bias in socioeconomic status has a direct influence on medical decision making (Haider et al, 2015;Pettit et al 2017), it is found that implicit bias is rather expressed in the behaviour towards patients. Physicians have been found to pay more attention to pain control and had a better communication with patients of a higher socioeconomic status, while the opposite has been true for patients of a lower socioeconomic status (Pettit et al, 2017). Similar results have been found for implicit racial bias.…”
Section: The Impact Of Biases On Diagnosis and Treatmentmentioning
confidence: 97%
“…11 Lower SES patients were described as more demanding, 30 less competent to self-manage pain 19,30 but more disabled. 19,30 They were also prescribed less opioids and guideline treatments, 16,[30][31][32]48 less referred to pain specialists and multidisciplinary treatments 30 and more likely to get generic pain medication 30,32,48 and psychoeducation recommendations. 19,30,32,48 These findings generally suggest that lower SES patients' pain is more likely underassessed/undermanaged.…”
Section: Introductionmentioning
confidence: 99%